A Decade of Development of Chromogenic Culture Media for Clinical Microbiology in an Era of Molecular Diagnostics - Perry, John D (Clinical microbiology reviews, 2017)
In the last 25 years, chromogenic culture media have found widespread application in diagnostic clinical microbiology. In the last decade, the range of media available to clinical laboratories has expanded greatly, allowing specific detection of additional pathogens, including Pseudomonas aeruginosa, group B streptococci, Clostridium difficile, Campylobacter spp., and Yersinia enterocolitica. New media have also been developed to screen for pathogens with acquired antimicrobial resistance, including vancomycin-resistant enterococci, carbapenem-resistant Acinetobacter spp., and Enterobacteriaceae with extended-spectrum β-lactamases and carbapenemases. This review seeks to explore the utility of chromogenic media in clinical microbiology, with particular attention given to media that have been commercialized in the last decade. The impact of laboratory automation and complementary technologies such as matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) is also assessed. Finally, the review also seeks to demarcate the role of chromogenic media in an era of molecular diagnostics.